PENGARUH BRAND IMAGE, BRAND QUALITY, BRAND TRUST TERHADAP BRAND LOYALTY PADA PRODUK MEREK PHILIPS - shelly; David Humala Sitorus (LPPM Universitas Putera Batam, 2022)
In companies in the field of industry need to make efforts to process quality and safe productswhen used by consumers. Then the company needs to pay attention to marketing strategiesin the progress of a product in the future, to increase sales and generate profits for thecompany. If the image and quality of the product is marketed well, it will certainly increasebrand loyalty. Here are the factors that affect brand loyalty, namely brand image, brandquality, and brand trust. The purpose of this study is to find out the influence of Brand Image,Brand Quality, Brand Trust on Brand Loyalty on Philips Brand Products. The sample numberof 100 people and respondents were consumers of Philips light products in Batam city usingpurposive sampling techniques. The type of research used is a quantitative approach withmultiple linear regression analysis tools.The results of this study show that Brand Image,Brand Quality, and Brand Trust simultaneously have a significant effect on Brand Loyalty onPhilips Brand Products and proven truth. While partially Brand Image, Brand Quality, andBrand Trust have a significant effect on the Brand Loyalty of Philips Brand Products andproven to be true. In conclusion, partially and simultaneously it was proven that Brand Image,Brand Quality, and Brand Trust had an effect of 52.9%. The remaining 47.1% were affectedby other variables not studied in the study.Keywords : Brand Image, Brand Quality, Brand Trust, and Brand Loyalty.